How can we help African American substance users stop smoking? client and agency perspectives. Issue 3 (3rd July 2019) - Berman, Barbara A.; Jones, Loretta; Jones, Felica; Jones, Andrea; Pacheco, Blanca Azucena; McCarthy, William J.
ABSTRACT: Research is needed to better understand barriers to smoking cessation and sustained abstinence among racial/ethnic minority polydrug users. We conducted community dialogue groups involving 49 clients in substance use treatment programs with predominantly ethnic minority clientele and individual dialogues/interviews with seven program providers (stakeholders). Most clients were African American, under 40 years old, women, current smokers, and high school graduates. Smoking cessation services in these programs were considered inadequate and community programs insufficiently culturally tailored and economically and geographically inaccessible. Participants discussed individual "willpower" and choice; agency tobacco-related programs and policies; the relationships between smoking, smoking cessation, and treatment goals; and steps needed to reshape agency services and policies to provide greater support for smoking cessation in this at-risk population.